Pelatihan Pengambilan Video dan Penulisan Caption Berbasis AI di KIM Senyum Tempel - Nazwa Kayla Arthalevia; Ariqoh Nur Afisyah; Annisa Nasywa Rizkia; Yulia Hananya Shinta; Rizkhy Fi Sabil Nur Fikri; M. Fadhil Saputra; Bernardus Sutatama Ginong Pratidina; Hans Hermang Mintana; Popi Andiyansari (Universitas Teknologi Yogyakarta, 2025)
A training session on video shooting techniques and caption writing based on artificial intelligence (AI) was conducted to improve the digital literacy of the Kelompok Informasi Masyarakat (KIM) Senyum Tempel community. The training was motivated by KIM members' limited ability to produce informative and interesting digital content suitable for social media. Implementation methods included interactive lectures, hands-on practice, and evaluation through pre- and post-tests. The material covered basic video shooting techniques using smartphones and AI-based caption writing based on the principles of citizen journalism. The results showed a significant increase in participants' understanding and skills, as indicated by an increase in average scores: from 65% to 86% for video shooting techniques and from 64% to 85% for AI-based caption writing. The training was effective in enhancing the participants' digital skills and encouraging KIM to optimize its role as a community-based information provider at the local level.